Global Discourse Analysis in Iraqi Journalism: A Critical Study of the Representation of International Issues in “Al-Bayyna Al-Jadida” Newspaper during 2024 (Eurasian Journal of Media and Communications, 2025)
This research aims to analyze global discourse in Iraqi journalism through a critical study of the representation of international issues in the “Al-Bayyna Al-Jadida” newspaper during the year 2024. The study examines the impact of political, economic, and cultural factors on how Iraqi journalism covers international issues, as well as the influence of the local media environment in shaping this discourse. The study reviews international issues addressed by the newspaper, such as political, economic, environmental crises, and human rights, and analyzes the discursive methods used to present these issues. Additionally, the research focuses on the journalistic approaches adopted in covering international events, such as analytical articles and breaking news, with an emphasis on the media framing that may influence the image constructed for the Iraqi reader.